Intermediate social studies explore. (Chicago : Encyclopaedia Britannica, 2001)
Contains activities designed to guide students through specific Internet sites related to social studies and help them better understand the information they are viewing.
"Intermediate Internet activities.".
Cover title: Scoial studies create explore.
Title from cover p. [4].
Professional
Keywords: Social sciences -- Computer-assisted instruction; Social sciences -- Study and teaching; Social sciences -- Computer-assisted instruction; Social sciences -- Study and teaching